Relationship between vitamin D, iron, and hepcidin in premenopausal females, potentially confounded by ethnicity. - Greenwood A; Von Hurst PR; Beck KL; Mazahery H; Lim K; Badenhorst CE (Springer Nature, 2023)
PURPOSE: To investigate the associations between vitamin D, hepcidin, and iron status in premenopausal females of different ethnic cohorts residing in Auckland, New Zealand (NZ). METHODS: A total of 160 females aged 18-45 years participated in a cross-sectional study. Demographics, body composition, serum 25(OH)D, inflammatory markers (C-reactive protein and interleukin-6, IL-6), and iron biomarkers (serum ferritin, haemoglobin, soluble transferrin receptor, and hepcidin) were measured. Comparisons between parametric, non-parametric, and categorical variables were completed by using one-way ANOVA, Kruskal-Wallis, and Chi-squared tests, respectively. ANCOVA was used to compare serum 25(OH)D across iron parameter categories. RESULTS: Of the 160 participants, 60 were NZ European, 67 were South Asian, and 33 were from the 'other' ethnic groups. South Asians had significantly higher body fat percentage (BF%) and IL-6 concentration (38.34% and 1.66 pg·mL-1, respectively), compared to NZ Europeans (27.49% and 0.63 pg·mL-1, respectively, p < 0.001). South Asians had significantly lower 25(OH)D concentrations compared to NZ Europeans (33.59 nmol·L-1 vs 74.84 nmol·L-1, p < 0.001). In NZ Europeans, higher 25(OH)D concentration was seen in those with lower (≤ 3.5 nM) hepcidin concentration, p = 0.0046. In South Asians, higher 25(OH)D concentration was seen in those with higher (> 3.5 nM) hepcidin concentrations, p = 0.038. There were no associations between serum 25(OH)D and serum ferritin. CONCLUSION: Within South Asian women, an unexpected positive relationship between 25(OH)D and hepcidin concentration was observed which may be due to significantly higher IL-6 concentrations, BF%, and lower 25(OH)D concentrations. Future research is required to confirm these observations in this ethnic cohort.
Keywords: Iron regulation; Serum 25(OH)D; Serum ferritin; South Asian; Vitamin D status; Female; Humans; Cross-Sectional Studies; Ethnicity; Ferritins; Hepcidins; Interleukin-6; Iron; Vitamin D; Vitamins; Adolescent; Young Adult; Adult; Middle Aged